Organizational Support, Workload, and Role Conflict in Work-Life Balance as a Driver of Directorate General of Taxes Employee Performance: A Study at Jember Tax Office - Rush Aviciena, Iqbal; Qomariyah, Nurul; Nyoman Putu Martini, Ni (International Journal of Management Science and Information Technology, 2024)
Improving employee performance as part of efforts to enhance organizational performance should be a priority to achieve effectiveness and efficiency in the management of government agencies, particularly at Directorate General of Taxes as one of strategic government institution. The research aims to investigate how work-life balance influences the performance of Directorate General of Taxes employees at Jember Tax Office. The factors examined include organizational support, workload, and role conflict. The method used in this research is Structural Equation Modeling-Partial Least Square (SEM-PLS). Data were collected through google form questionnaires filled by 91 employees of Jember Tax Office. The findings indicate that role conflict negatively impacts employee performance directly and indirectly through the mediation of work-life balance. Conversely, organizational support and workload do not directly affect employee performance but show a significant indirect influence through the mediation of work-life balance. The Directorate General of Taxes needs to consider the level of role conflict that may arise for employees with each policy being formulated. Management also needs to pay attention to the organizational support and workload implemented, as they indirectly affect employee performance through the mediation of work-life balance